Networks of prospective thoughts: The organisational role of emotion and its impact on well-being. Issue 3 (2nd April 2016) - Demblon, Julie; D'Argembeau, Arnaud
Abstract : Recent research has shown that many prospective thoughts are organised in networks of related events, but the relational dimensions that contribute to the formation of such networks are not fully understood. Here, we investigated the organisational role of emotion by using cues of different valence for eliciting event networks. We found that manipulating the emotional valence of cues influenced the characteristics of events within networks, and that members of a network were more similar to each other on affective components than they were to members of other networks. Furthermore, a substantial proportion of events within networks were part of thematic clusters and cluster membership significantly modulated the impact of represented events on current well-being, in part through an intensification of the emotion felt when thinking about these events. These findings demonstrate that emotion contributes to the organisation of future thoughts in networks that can affect people's well-being.